AEROSOLS AND OZONE : HOW REAL IS THE THREAT? - Herbert, Roy (SCHOOL SCIENCE, 2012)
There are fears that the ozone layer, high in the stratosphere, is under threat from man-made chemicals and will no longer shield us against harmful radiation as efficiently as in the past. But there is a lot yet to be learned about the atmosphere, for it is a bewilderingly complex reaction vessel. One thing is clear, that any pronouncements about stratospheric ozone should include plenty of provisos.